Penerapan Value Engineering pada Proyek Konstruksi di Masa Pandemi Covid-19 - Zulfiati, Ria; Handayani, Elvira; Saputra, Ade Rio (Universitas Batanghari, 2023)
Value Engineering is a function analysis approach that aims to reduce the cost of production or project. The amount of costs that will be needed both in the planning period and also the implementation and time saving process are sought not to increase the amount of cost itself. Gamil & Alhagar(2020) revealed that there are several impacts of Covid-19 in the construction sector, namely project suspensions, workers who lose their jobs, jobs that exceed the time limit, excessive costs, and financial impacts. Jallow et al (2020) stated the changes that must be made to the infrastructure sector in order to comply with health protocols and remain productive during lockdown. The problem in this study is how much the total cost savings can be obtained after Value Engineering method to the architectural work of the Facilities and Infrastructure Rehabilitation project at the Sungai Gelam Campground in the Hall Building. Through graphs and calculations is, the results of 4 work items with the highest percentage were obtained, namely on wall pair work, roofing work, floor formwork work, and frame, door and window work. At the creative stage, the idea of alternative replacements is given to the same quality, function and quality, but at a lower price. Then the analysis stage carries out the development of a comparison between the alternatives to be obtained. The recommendation stage is the result of the chosen alternative. At the recommendation stage, the result of applying the value engineering method is the Material used for the work of the red Masonry 5x11x22cm amounting to Rp.1,934,368.62 or 9.16% of the initial design cost. For Metal Tile Roofing Work of Rp.7,775,287.18 or 30.27% of the initial design cost. For Aluminum Frame, Door and Window Work, 8mm Glass is Rp.8,360,275 or 20% of the initial design cost. For Ceramic Floor Work measuring 40x40 cm (Plain) of Rp. 12,926,981.30 or 25.26% of the initial design cost. The cost efficiency that can be obtained using Rp. 30,996,912.10 or 6% of Rp. 514,217,599.92,- the total project